DISTRIBUTED LEDGER TECHNOLOGY IN THE BANKING SECTOR: ANALYSIS OF THE VALUE OF Information technology IN REDUCING THE FINANCIAL LOSS OF THE COMMERCIAL BANK - A. Mikhaylova (Вестник университета, 2017)
The article presents the results of a study of a business-engineering project for a commercial bank. The technique of the international standard of business analysis practice BABOK GUIDE v3 (SWOT-Analysis) is used to identify internal and external factors that affect the organization. The commercial bank «Home Credit» was chosen as the object of the study. The aim of the research is to achieve the leading position of a commercial bank among the world's credit institutions by developing a program for the transformation of the enterprise architecture segment. Business process «Lending« was subject to reengineering and reoriented to increase the share of solvent customers through the implementation of the Masterchain platform in the organization's activities. The potential results from the introduction of the «Blockchain» into the business process «Lending» are defined.